Determinants of Audit Delay: Evidance from Profitability, Leverage, Firm Size, and Audit Committe - Nabila Fary Adiyana; R Taufik Hidayat; Keri Boru Hotang (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence on the influence of profitability, leverage, company size, and audit committees on audit delay. Design/methodology/approach – This study uses quantitative research. It utilizes secondary data. The population is 67 industrial companies listed on the Indonesia Stock Exchange between 2020 and 2024. The sample is 27 industrial companies listed on the Indonesia Stock Exchange between 2020 and 2024. The total number of observations in this study is 135. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews9 software. Findings – The results of this study indicate that the profitability variable has a negative and significant effect on audit delay. The leverage variable has a positive and insignificant effect on audit delay. The company size variable has a negative and significant effect on audit delay. The audit committee variable has a positive and insignificant effect on audit delay. Research limitations/implications –. This study aims to provide information on audit delay and can be beneficial in decision-making as well as serve as a reference for further research.